Mitonuclear discordance modulates mitochondrial ageing dynamics in natural Drosophila populations - Stefano Bettinazzi; Avishikta Chakraborty; Finley Grover-Thomas; Damian K. Dowling; M. Florencia Camus (Proceedings of the National Academy of Sciences, 2026)
Mitochondrial decline is a hallmark of ageing, yet the role of intergenomic compatibility in shaping ageing trajectories remains poorly understood, particularly in an ecologically relevant framework. Hormetic interventions have been proposed as strategies to modulate metabolism and lifespan, but it is unknown how this operates in the context of mitonuclear discordance. Here, we demonstrate that mitonuclear mismatch accelerates age-related mitochondrial decline, elevates reactive oxygen species production, and shortens lifespan. Strikingly, early-life mitochondrial stress induced by dietary modulation counteracts these effects, promoting mitochondrial homeostasis and longevity. Our findings reveal mitonuclear interactions shaping ageing trajectories in natural populations and provide unique evidence that targeted interventions can act as a buffer against the detrimental impact of genetic discordance.